Psychological factors and entrepreneurial orientation: Could education and supportive environment moderate this relationship? - Asad Javed; Muhammad Yasir; Abdul Majid (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
The purpose of this study is to find out the role of individual's psychological factors in determining entrepreneurial orientation and to examine if the relationship could be moderated by non-psychological factors? Reflecting on competency theory as a specific theoretical foundation and resource based theory as an overarching theory, impact of four psychological factors i.e. self-confidence, internal locus of control, tolerance of ambiguity, and propensity to take risk and two non-psychological factors i.e. role of education and role of supportive environment were studied in relationship to their impact on entrepreneurial orientation. Unit of analysis of this cross sectional study was individual entrepreneurs operating their food-related business (retail outlets) at micro level. The results of survey explain that psychological factors affect entrepreneurial orientation and non-psychological factors moderate this relationship. Findings of this study can be adopted by high risk ventures capitalists to assess entrepreneurial capabilities to improve return on investment as well as by managers in the new employees hiring process.
Keywords: 330; entrepreneurial orientation; psychological factors; role of education; supportive environment